1996
DOI: 10.1002/mats.1996.040050401
|View full text |Cite
|
Sign up to set email alerts
|

The structure and phase transitions in polymer blends, diblock copolymers and liquid crystalline polymers: The Landau‐Ginzburg approach

Abstract: The polymer systems are discussed in the framework of the Landau-Ginzburg model. The model is derived from the mesoscopic Edwards hamiltonian via the conditional partition function. We discuss flexible, semiflexible and rigid polymers.The following systems are studied: polymer blends, flexible diblock and multi-block copolymer melts, random copolymer melts, ring polymers, rigid-flexible diblock copolymer melts, mixtures of copolymers and homopolymers and mixtures of liquid crystalline polymers. Three methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 109 publications
3
46
0
Order By: Relevance
“…The study of the structure, phase behavior and interfacial properties of polymers has found longstanding and widespread interest. [1][2][3][4][5][6][7][8][9][10] Understanding the phase behavior of mixtures of different kinds of polymers is important scientifically 11 as well as practically. The scientific importance arises from the complex behavior polymer mixtures display, and the practical importance arises from the many industrial applications of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the structure, phase behavior and interfacial properties of polymers has found longstanding and widespread interest. [1][2][3][4][5][6][7][8][9][10] Understanding the phase behavior of mixtures of different kinds of polymers is important scientifically 11 as well as practically. The scientific importance arises from the complex behavior polymer mixtures display, and the practical importance arises from the many industrial applications of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…A consideration of the thermodynamic behavior of an incompressible melt of binary heteropolymers in the framework of the WSL theory [16][17][18][19][20] …”
Section: Microscopic Wsl Theorymentioning
confidence: 99%
“…, , Γ q q q % [16][17][18][19][20]. The chemical structure of a macromolecule is known to be completely characterized by the set of chemical correlators [21,22].…”
Section: Microscopic Wsl Theorymentioning
confidence: 99%
See 2 more Smart Citations